1977
DOI: 10.1111/j.1745-4557.1977.tb00997.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF ELECTRICAL STIMULATION ON THE RATE OF POST‐MORTEM GLYCOLYSIS IN SOME BOVINE MUSCLES1

Abstract: Processing beef prior to the onset of rigor results in an unsatisfactory product. Stimulation will hasten rigor by accelerating post‐mortem metabolism. The purpose of this manuscript is to describe the effect of electrical stimulation on the rates of post‐mortem glycolysis in the choice bovine carcass. Sides of six choice carcasses weighing 310–367 kg were stimulated for 30 min beginning an hour after death. Seven carcasses were stimulated for 15 min beginning 30 min post‐mortem. In each instance the opposite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 46 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Several research workers have demonstrated the effect of electrical stimulation postmortem on pH decline and the development of rigor (Bendall 1976;Bouton et al 1978;Carse 1973;Chrystall and Hagyard 1976;Chrystall and Devine 1978;Davey et al 1976;McCollum and Henrickson 1977;Nichols and Cross 1980;Shaw a n d Walker 1977;Taylor and Marshall 1980). Electrical stimulation markedly accelerated glycolysis (Chrystall and Hagyard 1976;Davey et al 1976) and reduced the time for the onset of rigor mortis ).…”
Section: Rate Of Glycolysismentioning
confidence: 99%
See 1 more Smart Citation
“…Several research workers have demonstrated the effect of electrical stimulation postmortem on pH decline and the development of rigor (Bendall 1976;Bouton et al 1978;Carse 1973;Chrystall and Hagyard 1976;Chrystall and Devine 1978;Davey et al 1976;McCollum and Henrickson 1977;Nichols and Cross 1980;Shaw a n d Walker 1977;Taylor and Marshall 1980). Electrical stimulation markedly accelerated glycolysis (Chrystall and Hagyard 1976;Davey et al 1976) and reduced the time for the onset of rigor mortis ).…”
Section: Rate Of Glycolysismentioning
confidence: 99%
“…Studies involving electrical stimulation have been conducted on beef, (Bendall and Rhodes 1976;Bouton et al 1978;Calkins et al 1980;Demeyer and Vanderndriessche 1980;Dutson et al 1980aDutson et al , 1980bHall et al 1980;Jeremiah and Martin 1980;Judge et al 1980;McCollum and Henrickson 1977;Nichols and Cross 1980;Ray et al 1980;Ruderus 1980;Savell et al 1978aSavell et al , 197813, 1978cSavell et al 1977;Savell et al 1979;Shaw and Walker 1977;Smith et al 1977;Sorinmade et al 1978;Taylor and Marshall 1980;Will et al 1979 lamb, (Bendall 1976;Carse 1973;Hagyard 1975, 1976;Chrystall et al 1980;Riley et al 1980aRiley et al , 1980bSavell et al 1977;Smith et al 1980), rabbit (Bendall 1976), pork (Hallund and Bendall 1965;Smith et al 1980;Westervelt and Stouffer 1978), goat (McKeith et al 1979;Savell et al 1977;Smith et al 1980) and chicken (DeFremery and Pool 1960).…”
Section: Introductionmentioning
confidence: 99%
“…The application of postmortem electrical stimulation technology in meat science has helped to reduce the length of the delay in chilling time from 9-12 hr to 1-3 hr Chrystall and Devine 1978;McCollum and Henrickson 1980). This also reduces the risk of bacterial multiplication which would be likely during high temperature conditioning of the carcasses.…”
Section: Electrical Stimulationmentioning
confidence: 99%
“…Presently, precise metabolic activity in cells is measured by showing entrainment of heterogeneous glycolytic oscillations in single cells [11] [ 12], in which work was one of the vast news of the year. Interaction of glycolysis with external electric field stimulation has been known for a long time [13] [14] [15]. Our objective is to clear the following question in detail: are there any similarities between the temperature stimuli and electric stimuli in transient glycolytic oscillation?…”
Section: Introductionmentioning
confidence: 99%